Abnormal Blink Reflex and Intermuscular Coherence in Writer's Cramp - Choudhury, Supriyo; Singh, Ravi; Chatterjee, Payel; Trivedi, Santosh; Shubham, Shantanu; Baker, Mark R.; Kumar, Hrishikesh; Baker, Stuart N. (Frontiers in Neurology, 2018)
Background: Writer’s cramp (WC) is a task-specific focal hand dystonia presenting with pain, stiffness and/or tremor while writing. We explored the involvement of cortical and brainstem circuits by measuring intermuscular coherence (IMC) and pre-pulse inhibition of the blink reflex. Methods: IMC was measured in 10 healthy controls, 20 WC patients (10 with associated tremor) while they performed a precision grip task at different force levels. Blink responses were evaluated in 9 healthy controls and 10 WC patients by stimulating the right supraorbital nerve and recording surface EMG from the orbicularis oculi muscles bilaterally. Pre-pulse inhibition involved conditioning this stimulation with a prior shock to the right median nerve (100ms interval), and measuring the reduction in the R2 component of the blink reflex. Results: Significant IMC at 3-7Hz was present in WC patients, but not in healthy controls. Compared to healthy controls, in WC patients the R2 component of the blink reflex showed significantly less pre-pulse inhibition. IMC at 3-7 Hz could reliably discriminate WC patients from healthy controls. Conclusion: Cortical or sub-cortical circuits generating theta (3-7Hz) oscillations might play an important role in the pathogenesis of WC. Moreover, the lack of pre-pulse inhibition implicates abnormalities in brainstem inhibition in the emergence of WC. IMC may merit further development as an electrodiagnostic test for focal dystonia.